The Impact of Macroeconomic Indicators on Medical Tourism: A Global Perspective - Geitona, Mary; Giannake, Georgia; Zavras, Dimitris; Latsou, Dimitra (Advances in Social Sciences Research Journal, 2024)
Medical tourism is an expanding global phenomenon stimulating economic development driven by a combination of multiple macro and socioeconomic factors. The study aims to investigate whether the development of medical tourism globally is associated with specific macroeconomic indicators. The association of Medical Tourism Index (MTI) is explored with Gross Domestic Product (GDP), healthcare spending and international tourism receipts. A countries’ grouping method and an ordinary least squares (OLS) regression model were used. MTI was used as the outcome variable, while macroeconomic indicators as potential predictors. The grouping of countries showed that European and Asian countries as well as Canada excel high ranking in all indicators. However, the Gulf Cooperation Council countries (GCC) that exhibit high performance in GDP, rank below the MTI average. Caribbean and Latin American countries are ranking high in the MTI but fall below the average in all the indicators. The OLS analysis showed a positive correlation between the score of the MTI and health expenditure and no correlation among MTI, GDP and international tourism receipts, a finding also supported by the grouping analysis. Taking into consideration the similarities and disparities found among countries regarding the macroeconomic indicators mostly impacting medical tourism, it seems that there is a consensus on their relationship but not clearly identified rather due to a variety of social, cultural and ethical factors that dominate in each country. Further research is needed in order to obtain more robust and comparative evidence.